Near-field optics on flatland: from noble metals to van der Waals materials. Issue 1 (1st January 2019) - Duan, Jiahua; Li, Yafeng; Zhou, Yixi; Cheng, Yuan; Chen, Jianing
ABSTRACT: Near-field optics, with the capability for nanoscale manipulation of photons and enhancement of light-matter interactions, has drawn tremendous attentions in recent years. Compared with traditional noble metals, near-field optics in low-dimensional van der Waals (vdW) materials has revealed various polaritonic modes with gate-tunable competence, high confinement and novel quantum physics. Advanced near-field imaging technique, named scattering-type scanning near-field optical microscopy, allows launching and visualizing the polaritonic waves in both noble metals and vdW materials. In this review, we introduce the fundamental principles of near-field optics and summarize up-to-date near-field studies and related quantum physics in three aspects: (1) In-situ electric field distribution around metallic nanostructures; (2) various polaritons in vdW materials and heterostructures; (3) quantum physical phenomena related to near-field optics in low-dimensional system. Then, we discuss the state-of-the-art near-field optics combing imaging with spectroscopy, transient measurement or Terahertz lasers for revealing new physics. To conclude, we summarize the nowadays challenges and present perspectives in the near-field optics field. Graphical Abstract: